The effect of residual hydrocarbons in soil following oil spillages on the growth of Zea mays plants. (October 2020) - Grifoni, M.; Rosellini, I.; Angelini, P.; Petruzzelli, G.; Pezzarossa, B.
Abstract: Liquid hydrocarbon pipeline accidents, including leaks due to the illegal or unauthorized collection of petroleum from oil pipelines, are a widespread phenomenon that can lead to pollution that may negatively affect soil quality and plant growth. The aim of this study is to evaluate hydrocarbon uptake and accumulation in Zea mays plants grown on soil affected by spills of fossil fuels. The experiments were conducted in microcosm, mesocosm and field tests. The potential transfer of contaminants from soil to plant and their effects on plant growth were investigated. The results from both the laboratory and field experiments showed that the plants grew better in the uncontaminated soil than in the soil polluted by hydrocarbons. Despite their significantly lower aerial biomass, plants grown in contaminated soil did not show any significant differences in C > 12 concentration, either in shoots or roots, compared to the control plants. Thus, the decrease in plant yield might not be attributed to hydrocarbons accumulation in the plant tissues and may rather be due to a reduced soil fertility, which negatively affected plant growth. Under our experimental conditions, the hydrocarbons present in the contaminated soil were not absorbed by the plants and did not accumulate in plant tissue or in grains, thus avoiding the risk of them entering the food chain. Graphical abstract: Image 1 Highlights: Oil spillage negatively affected chemical and physical properties of soil. Petroleum hydrocarbons (PHCs) in soil reduced the growth of Zea mays plants. PHCs content in Zea mays grown in contaminated and control soils did not differ. Results suggest a biogenic rather than anthropogenic origin of the PHCs in plants. Abstract : "PHC reduced soil fertility, negatively affecting plant growth. Our findings suggest that PHC in soil were not absorbed by the maize and did not accumulate in its tissues".